Guerres, individus, systèmes : problématiques de l’écriture martiale dans le roman américain du XXème siècle - Julien Brugeron (Vernacular: New Connections in Language, Literature, & Culture, 2021)
This article aims at reassessing the long 20th century American war novel and its inherent and hitherto seldom addressed problematics. Borrowing from both French, American and English critical standpoints, it aims at clarifying the definitional, ethical, political and aesthetic aspects of war writing by putting on an equal footing classic works of the genre (Dos Passos, Mailer, Heller, Herr) and left-aside writers (La Motte, Boyd, Hasford) as well as contemporary novelists (Powers). It is critical in American literary history, and to literary history in general, to seize what is at stake in war writing, as this particular kind of aesthetics showcases the crucial stakes of novel writing throughout the 20th and 21st centuries: what can one write, where does the narrative voice come from, what is it threatened by and how to resist the multiple threats?
Keywords: roman américain; guerre; éthique; politique; conflits